Oncogenic K-Ras Activates p38 to Maintain Colorectal Cancer Cell Proliferation during MEK Inhibition - Winan J. van Houdt; Menno T. de Bruijn; Benjamin L. Emmink; Danielle Raats; Frederik J. H. Hoogwater; Inne H. M. Borel Rinkes; Onno Kranenburg (Cellular Oncology)
Background: Colon carcinomas frequently contain activating mutations in the K-ras proto-oncogene. K-ras itself is a poor drug target and drug development efforts have mostly focused on components of the classical Ras-activated MEK/ERK pathway. Here we have studied whether endogenous oncogenic K-ras affects the dependency of colorectal tumor cells on MEK/ERK signaling.